Neuronal guidance behaviours: the primary cilium perspective - Atkins, Melody; Fassier, Coralie; Nicol, Xavier (Frontiers in Cell and Developmental Biology, 2025)
The establishment of functional neuronal circuits critically relies on the ability of developing neurons to accurately sense and integrate a variety of guidance signals from their surrounding environment. Such signals are indeed crucial during key steps of neuronal circuit wiring, including neuronal migration and axon guidance, to guide developing neurons or extending axons towards their target destination in the developing brain. The growth cone, located at the tip of developing neurons, is a key subcellular structure in this process, that concentrates many different guidance receptors and signalling molecules and specialises in the probing and integration of extracellular signals into various guidance behaviours. Interestingly, the small primary cilium, long considered as a vestigial organelle, has progressively emerged as a cellular antenna specialised in cell signalling, and has been reported, just like the growth cone, to harbour a variety of guidance receptors. How primary cilium-elicited signals are then transduced into specific cellular processes to guide developing neurons and axons remains however obscure. In this review, we will summarise our emerging understanding of the role of primary cilium-elicited signalling pathways on neuronal guidance processes, by focusing on neuronal migration and axon guidance. We will highlight the primary cilium molecular diversity, and how it shapes the primary cilium functional versatility, allowing the ciliary compartment to instruct various guidance behaviours through the regulation of different cellular processes. We will moreover discuss current and future avenues of research, to unravel the different molecular effectors activated downstream of specific ciliary signals, and clues to be gained from studies performed in non-neuronal cells. Rising challenges of the field will also be addressed, such as the technical challenge induced by the dual subcellular localisation (i.e., ciliary and extra-ciliary) of many ciliary guidance receptors, and the importance of the development of new genetic/chemo-genetic/optogenetic tools. Finally, we will highlight the insight such studies will bring for our understanding of the aetiology of different disorders, including ciliopathies, neurodevelopmental and neurodegenerative disorders, but also cancer cell migration/invasion, which are associated with defective primary cilium formation and function.